2014
DOI: 10.1107/s2053230x14023188
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification and X-ray crystallographic analysis of theHelicobacter pyloriblood group antigen-binding adhesin BabA

Abstract: Helicobacter pylori is a human pathogen that colonizes about 50% of the world's population, causing chronic gastritis, duodenal ulcers and even gastric cancer. A steady emergence of multiple antibiotic resistant strains poses an important public health threat and there is an urgent requirement for alternative therapeutics. The blood group antigen-binding adhesin BabA mediates the intimate attachment to the host mucosa and forms a major candidate for novel vaccine and drug development. Here, the recombinant exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…We previously found that residues 25–460 of the mature 721 residue BabA formed a stable, crystallizable fragment (hereafter dubbed BabAadhesin domain or BabA AD )(Subedi et al, 2014). Isothermal titration calorimetry (ITC) showed strain 17875 BabA AD bound Le b , with a monovalent binding interaction with a low micromolar dissociation constant (Kd) of 80.0 ± 7.1 μM (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that residues 25–460 of the mature 721 residue BabA formed a stable, crystallizable fragment (hereafter dubbed BabAadhesin domain or BabA AD )(Subedi et al, 2014). Isothermal titration calorimetry (ITC) showed strain 17875 BabA AD bound Le b , with a monovalent binding interaction with a low micromolar dissociation constant (Kd) of 80.0 ± 7.1 μM (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Crystal growth was facilitated with one of two nanobodies (Nb-ER14 or Nb-ER19) generated against native BabA purified from H. pylori found to stabilize the recombinant BabA AD fragment (Figure S1B) (Subedi et al, 2014). Both Nbs specifically bound to BabA-expressing H. pylori cells, demonstrating that the conformation of Nb-stabilized BabA AD is equivalent to that of native BabA in the bacterial outer membrane (Figure S1C).…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structures of BabA and of the homologous adhesin SabA was recently resolved [ 61 , 62 ] giving new insights into how H. pylori adhesion is mediated on sequence level. Comparing the BabA sequence to the SabA protein structure shows that there are several regions of high positive selection in the region where BabA and SabA do not share homology (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, additional evidence for this virulence role was provided by an epidemiological study that showed a significant association between the combination of OipA, BabA, and SabA and a diagnosis of H. pylori -associated gastric cancer (Su et al, 2016). However, recent investigations have reiterated that H. pylori BabA sequences, expression, and corresponding binding phenotypes are highly diverse and dynamic (Bugaytsova et al, 2017; Hansen et al, 2017; Kable et al, 2017; Moonens and Remaut, 2017; Subedi et al, 2014; Sweeney and Guillemin, 2016). Thus, caution is needed when suggesting an association between babA and clinical outcomes based on epidemiological studies.…”
Section: New Insights On H Pylori Virulence Factorsmentioning
confidence: 99%